The Differing Effects of Symbolic Interpretation and Inclusion of Transcendence on Life Goals and Mental Health in Hungarian Adults - Zábó, Virág; Faragó, Laura; Vargha, András; Wooley, Lisa (Central European Journal of Educational Research, 2020)
This study aimed to investigate the influence of religious attitudes, namely Inclusion of Trancendence and Symbolic Interpretation on life goals and different aspects of mental health.Participants (N = 604) filled in an online questionnaire including the Post-Critical Belief Scale (Martos et al., 2009), the short version of Aspiration Index (Martos et al., 2006), and the Mental Health Test (MHT; see Oláh et al., 2018).We investigated the relationship between religious attitudes, life goals, and the subscales of mental health using path analyses. The Symbolic Interpretation of religious content predicts support for intrinsically motivated life goals, while the Inclusion of Transcendence predicts the refusal of extrinsic aspirations. Positive effects were revealed between the Inclusion of Transcendence and global well-being, strategies aim at creating and enchancing happiness, and resilience. Symbolic Interpretation was positively related to creative, executing individual and social efficiency, while negatively influenced resilience.The Inclusion of Transcendence and Symbolic Interpretation separately predict different aspects of life goals and mental health, and jointly support a higher quality of life.